Modelling and simulation of surface plasmonic resonance in photonic crystal fiber / Rifat Ahmmed Aoni - Rifat, Ahmmed Aoni (2015)
Surface Plasmon Resonance (SPR) refers to the coupling between the electromagnetic wave and the surface plasmonic wave (SPW) on the surface between a metal and a dielectric medium. Since last decade, the SPR behavior is widely applied in prism based SPR sensor, which is bulky and not suitable for remote monitoring applications. To overcome this limitation, photonic crystal fiber (PCF) based SPR sensor had attained great attention with the advantages of easily launching light through the fiber, small-size and design flexibility. To establish the SPR phenomena, metal deposition is necessary. Nowadays, in most of the PCF-SPR sensors, metal is selectively deposited inside the airholes with numerous selective metallic and liquid channels, which made fabrication of such sensors impractical or very challenging. In this dissertation, four different PCF-SPR sensors are introduced with relatively high or comparable sensing performance. The proposed sensors are numerically investigated using the commercial Multiphysics COMSOL software. First study presents the PCFSPR sensor with only one graphene-silver deposited channel and two high refractive index (RI) liquid channels. It shows the amplitude sensitivity as high as 418 RIU-1 and the wavelength interrogation sensitivity of 3000 nm/RIU. In the second study, focusing on the metal deposition problem, a flat structure PCF-SPR sensor is developed where, the metal layer is deposited outside the fiber structure and the sensor will perform the external sensing scheme to detect the analytes. The proposed flat SPR sensor enhances the evanescent field resulting the amplitude sensitivity as high as 820 RIU-1 and the remarkable wavelength interrogation sensitivity of 23,000 nm/RIU. In the third study, a practically simple PCF SPR sensor is proposed. The metallic layer and sensing layer are placed outside the fiber structure which makes the sensor configuration simple and the analyte detection process easier. The proposed sensor shows the amplitude and wavelength interrogation sensitivity of 320 RIU-1 and 4000 nm/RIU, respectively. In the last work, copper is utilized in PCF SPR sensor for the first time due to its long-term stable sensing performance; and graphene is used to prevent copper oxidation and enhance the sensor performance. Similar to the third design, here the metallic layer and sensing layer are positioned outside the fiber structure resulting easy detection mechanism. It shows the wavelength interrogation sensitivity of 2000 nm/RIU with the sensor resolution of 5×10-5 RIU. Due to the promising sensitivity, the proposed sensors would be potential candidates for chemical, bio-chemical, organic chemical and organic molecule analytes detection with realizable structure.